Anticancer Potencies of PtII‐ and PdII‐linked M2L4 Coordination Capsules with Improved Selectivity. Issue 4 (23rd December 2015) - Ahmedova, Anife; Momekova, Denitsa; Yamashina, Masahiro; Shestakova, Pavletta; Momekov, Georgi; Akita, Munetaka; Yoshizawa, Michito
Abstract: Pt II ‐ and Pd II ‐linked M2 L4 coordination capsules, providing a confined cavity encircled by polyaromatic frameworks, exhibit anticancer activities superior to cisplatin against two types of leukemic cells (HL‐60 and SKW‐3) and pronounced toxicity against cisplatin‐resistant cells (HL‐60/CDDP). Notably, the cytotoxic selectivities of the Pt II and Pd II capsules toward cancerous cells are up to 5.3‐fold higher than that of cisplatin, as estimated through the non‐malignant/malignant‐cells toxicity ratio employing normal kidney cells (HEK‐293). In addition, the anticancer activity of the coordination capsules can be easily altered upon encapsulation of organic guest molecules. Abstract : Capsules combat cancer : Pt II ‐ and Pd II ‐linked M2 L4 coordination capsules exhibited anticancer activities superior to cisplatin against two types of leukemic cells and pronounced toxicity against cisplatin‐resistant cells. Notably, the cytotoxic selectivities of the Pt II and Pd II capsules toward cancerous cells are up to 5.3‐fold higher than that of cisplatin, as estimated through the non‐malignant/malignant‐cells toxicity ratio employing normal kidney cells.